ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KEMUNGKINAN TERJADINYA FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2015 – 2017 - Annas Thobroni, 15.05.52.0239; Wardjono, Wardjono (Students' Journal of Accounting and Banking, 2019)
This study aims to examine and analyze the factors that influence the likelihood of financial distress in manufacturing companies listed on the Indonesia stock exchange for the period 2015-2017. The population in this study are all Manufacturing Companies Registered on the Stock Exchange of the 2015-2017 Period. The sample selection uses the purpose sampling method. The analytical tool used in this study is logistic regression analysis. The test results show that liquidity and Company size have a significant negative effect on financial distress. Leverage has a significant positive effect on financial distress. While Profitability and Institutional Ownership do not have a effect on financial distress.